Histopathological effects of the herbicide atrazine on gills of the Brazilian endemic bivalve Diplodon expansus - Nogarol, Larissa Rosa [UNESP]; Brossi-Garcia, Ana Luiza [UNESP]; de Souza, Raphael Bastão [UNESP]; Fontanetti, Carmem Silvia [UNESP] (Taylor & Francis, 2016)
Due to their benthic filter-feeding habits and high bioaccumulation potential of metals and organic compounds, bivalve molluscs have been widely used in studies in the field and laboratory to assess the toxic effects of several compounds discharged in rivers, oceans and estuaries. However, most ecotoxicological studies use invasive exotic species, while the response of native species is poorly known. The Brazilian endemic species Diplodon expansus occurs in rivers near areas of intense agricultural activity, and atrazine is currently one of the main residues of pesticides found in water bodies of the Brazilian territory. This study was aimed at examining the toxicity of different atrazine concentrations to a Brazilian native mollusc by analysing the histology, histochemistry and ultrastructure of its gill filaments. The cells that comprise the frontal and intermediary regions of gill filaments were the most affected by the herbicide and responses associated with damage and protection were observed. The response of tissues and cells were dose-dependent. Higher concentrations of herbicide caused more severe alterations in large areas of the gills. The persistence of the alterations observed might result in severe functional problems in the gills of these animals, negatively affecting their performance and health.
Keywords: agrochemical; ecotoxicology; histochemistry; Morphology; mussel; ultrastructure